Respuesta :
The function that will sum up to 7x^2−11x+3 are f(x)=−x^3+x^2+3 and g(x)=x^3+6x^2−11x
Sum and difference of functions
Given the function
(f+g)(x)=7x^2−11x+3
We need two functions f(x) and g(x) that will sum up to 7x^2−11x+3
looking at the functions f(x)=−x^3+x^2+3 and g(x)=x^3+6x^2−11x
f(x) + g(x) = −x^3+x^2+3 + x^3+6x^2−11x
f(x) + g(x) = x^2 + 6x^2 −11x + 3
f(x) + g(x) = 7x^2 - 11x + 3
Hence the function that will sum up to 7x^2−11x+3 are f(x)=−x^3+x^2+3 and g(x)=x^3+6x^2−11x
Learn more on sum of functions here: https://brainly.com/question/17431959